Emotion recognition in generalized anxiety disorder, panic disorder, body dysmorphic disorder, skin picking disorder, trichotillomania, and posttraumatic stress disorder: a systematic review - Grace L. Wheeler; Shari A. Steinman (Frontiers in Psychology, 2025)
This systematic review evaluates patterns of emotion recognition in anxiety, obsessive-compulsive and related, and trauma- and stressor- related disorders (generalized anxiety disorder, panic disorder, body dysmorphic disorder, skin picking disorder, trichotillomania, and posttraumatic stress disorder). A comprehensive literature search identified 15 studies. Emotion recognition patterns were reviewed for each disorder. After considering strengths and weaknesses of individual studies and the literature as a whole, trends across disorders support a decreased recognition of sadness and an anger interpretation bias (i.e., tendency to see anger when other emotions are displayed). Conclusions are limited by a lack of covariate analyses and task validation. Future studies should investigate whether comorbid depression, transdiagnostic factors, and/or clinical severity may better explain variability in emotion recognition deficits.